The possibility analysis of Esports becoming an Olympic Sport - Wu, Y. (Haaga-Helia University of Applied Science, 2019)
Since Esports became a demonstration sport of the Jakarta Asian games, people have been wondering whether Esports will become an official event in the Olympics and Asian games. But as the events for the 2024 Paris Olympics and the 2022 Asian games in Hangzhou were announced, Esports is not included. The purpose of this study is to find out the factors of Esports becoming an Olympic sport and discuss the feasibility of turning Esports into an Olympic project.